The passenger pigeon - Fuller, Errol (Princeton University Press, 2015)
This illustrated book tells the story of North America's Passenger Pigeon, a bird species that--like the Tyrannosaur, the Mammoth, and the Dodo--has become one of the great icons of extinction.